A comparative study on the effect of calcitriol and cinacalcet on hyperparathyroidism in hemodialysis patients; a double-blinded randomized clinical trial - Saeed Mardani; Faranak Sadat Filsouf (Society of Diabetic Nephropathy Prevention, 2022)
Introduction:Chronic kidney disease (CKD) has lots of complication like calcium and phosphate metabolism disorders, hyperparathyroidism, vitamin D deficiency and metabolic acidosis. Objectives: The aim of this study was to determine and compare the effect of calcitriol and cinacalcet on hyperparathyroidism in hemodialysis patients due to end-stage renal disease (ESRD). Patients and Methods: This study was a double-blinded randomized clinical trial, which was conducted on 60 hemodialysis patients in 2017-2018. The patients were randomly assigned to two groups of 30 patients, which one group was treated with cinacalcet and the other group was treated with calcitriol. During this study, phosphorus, calcium and iPTH were measured. Results: The results showed that in the group treated with cinacalcet, the amount of calcium [t(22)=0.294, P>0.05] and the amount of phosphorus [t(22)=1.87, P>0.05] did not change significantly while iPTH values before and after the study had statistically significant difference [t(22)=4.37, P<0.05]. In group treated with calcitriol, the calcium, phosphorus and iPTH values did not change significantly (P>0.05). Calcium changes in the cinacalcet group compared to the calcitriol group [t (47) =-1.14, P>0.05] and also, the amount of phosphorus changes [t (47) =-1.022, P>0.05] was not statistically significant. The iPTH changes were not statistically significant between the two groups however iPTH in the calcitriol group was higher than the cinacalcet group [t (47) =-1.13, P>0.05]. Conclusion: In contrast to calcitriol, cinacalcet significantly reduced iPTH and did not significantly change calcium and phosphorus levels. Trial Registration: The trial was registered by Iranian Registry of Clinical Trials (IRCT) (identifier: IRCT20190702044076N1; https://en.irct.ir/trial/40547, Ethical code# IR.SKUMS.REC.1397.026).